Exploring the secrets of virus entry: the first respiratory syncytial virus carrying beta lactamase - De Ávila-Arias, Marcio; Villarreal-Camacho, Jose Luis; Cadena-Cruz, Christian; Hurtado-Gómez, Leidy; Costello, Heather M.; Rodriguez, Alexander; Burgos-Florez, Francisco; Bettin, Alfonso; Kararoudi, Meisam Naeimi; Muñoz, Amner; Peeples, Mark E.; San-Juan-Vergara, Homero (Frontiers in Microbiology, 2024)
Background Respiratory Syncytial Virus (RSV) presents a significant health threat, especially to young children. In-depth understanding of RSV entry mechanisms is essential for effective antiviral development. This study introduces an innovative RSV variant, featuring the fusion of the beta-lactamase (BlaM) enzyme with the RSV-P phosphoprotein, providing a versatile tool for dissecting viral entry dynamics. Methods Using the AlphaFold2 algorithm, we modeled the tertiary structure of the P-BlaM chimera, revealing structural similarities with both RSV-P and BlaM. Functional assessments, utilizing flow cytometry, quantified beta-lactamase activity and GFP expression in infected bronchial epithelial cells. Western blot analysis confirmed the integrity of P-BlaM within virions. Results The modeled P-BlaM chimera exhibited structural parallels with RSV-P and BlaM. Functional assays demonstrated robust beta-lactamase activity in recombinant virions, confirming successful P-BlaM incorporation as a structural protein. Quercetin, known for its antiviral properties, impeded viral entry by affecting virion fusion. Additionally, Ulixertinib, an ERK-1/2 inhibitor, significantly curtailed viral entry, implicating ERK-1/2 pathway signaling. Conclusions Our engineered RSV-P-BlaM chimera emerges as a valuable tool, illuminating RSV entry mechanisms. Structural and functional analyses unveil potential therapeutic targets. Quercetin and Ulixertinib, identified as distinct stage inhibitors, show promise for targeted antiviral strategies. Time-of-addition assays pinpoint quercetin’s specific interference stage, advancing our comprehension of RSV entry and guiding future antiviral developments.